Aging-dependent skin microbiome alterations across body sites in a United Kingdom cohort - Swaney, Mary Hannah; Newman, Duncan J.; Mao, Junhong; Hilton, Anthony C.; Worthington, Tony; Li, Min (Frontiers in Aging, 2025)
IntroductionThe aging process profoundly influences not only the health and visual appearance of the skin, but also the composition of the microbial communities residing on its surface.MethodsTo investigate these microbial changes, we employed a comprehensive, multi-scale approach that probes community composition, species interactions, and predicted metabolic function of the skin microbiome of the face and forearm in young and old age individuals from the United Kingdom using 16S rRNA gene sequencing.ResultsOur findings revealed significant and site-specific age-related shifts in the microbiome involving diversity, interpersonal heterogeneity, network connectivity, and metabolic potential, suggesting loss of microbiome robustness and a shift towards a hyperdiversified, fragile microbial community in old age. Furthermore, we applied Dirichlet Multinomial Mixtures to uncover novel age-driven microbiome profiles unique across each skin site, highlighting Cutibacterium acnes, Staphylococcus hominis, and microbial community diversity as key differentiating biomarkers of the skin microbiome across the lifespan.DiscussionOverall, through examining the aging skin microbiome from a systems perspective, our study reinforces and enhances the findings from previous aging microbiome studies and underscores the importance of site-specific differences in skin microbiome dynamics with age. These insights suggest that microbial interventions could mitigate age-related changes, enhancing skin health and wellbeing throughout life.